Strategi Pengelolaan Konflik dan Perubahan di Organisasi Remaja Masjid Al-Himmah Sidoarjo - Aji Wahyu Susanto; Anggita, Aulia Dwi Anggita (Fakultas Tarbiyah IAIN Kediri, 2024)
In response to the challenges that arise in managing religious communities, this research investigates and analyzes various approaches to managing conflict in mosque youth. This research uses a holistic approach to identify important phases in conflict management, starting from initial identification, open discussion, to mediation and negotiation. The main focus of research is training in mediation skills, the application of effective communication methods, and an in-depth understanding of the main causes of conflict. This research found that to achieve sustainability and harmony in mosque youth management, a sustainable conflict management strategy, which includes implementation of agreements, regular monitoring, and continuous evaluation, is necessary. This research increases understanding of how religious communities can effectively handle conflict to build a solid foundation for continued growth and sustainability. Keywords: conflict, mediation, mosque youth